(3QhVI GdCdHGH hJMaI GdCMHGH hHZjI GdWdGH hfNHI GdCMSGH deYQaI GdCfSGHs - (3GHf GdeDjO , eMeO Hf YHO Gddg Hf Ydj Hf GdMSjf Hf YR GdOjf, CHh YdGeI,J (B1031 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdegeGJ GdCNQhjI MH GdYJQI GdeWgQI GdfHhjI hMaX GdCfSGH GdecQeI GdeUWahjI hbO GYJfi HVHW CfSGHge GdYdeGA GdCYdGe s
(3BNQgG (B:s
(3hBNQg QSe TLQI fhM Hf dec s
(3GfXQ Qbe (B1083 (3JGQjNs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B226s
Keywords: (3GdJGQjNs